Relevant environmental issues - Salati, Eneas; Santos, Ângelo Augusto dos; Klabin, Israel (Estudos Avançados, 2006)
THIS PAPER indicates the environmental issues that must necessarily be approached, in Brazil, in a near future (2022). A study was made on some aspects of the effects of deforestation and Global Climate Change. A temperature rise around 0,78% has been observed during period of 1917 and 2003 in the Piracicaba region. For the Amazon region a rise of 0,56% was observed the 20th Century. The existing information indicates that not only deforestation but also Global Climate Changes act upon temperature rise. Deforestation has direct influence in precipitation decrease. The consequences of Global Climate Change are still unknown, being that some models indicate a precipitation rise and others a decrease. Deforestation also provokes great biodiversity loss, estimated between 8.000 to 34.000 species, considering that deforestation raises 1% per year.